Workshop Public Speaking Bagi Guru SD Berbasis Storytelling Di Kota Semarang - Naiza Rosalia; Mutia Rahmi Pratiwi; Mukaromah Mukaromah (ACADEMICS IN ACTION Journal of Community Empowerment, 2023)
Changes in the world of education require teachers to continue to be creative in delivering subject, no longer conventionally. The diversity of media and technological developments require teachers to actively develop their potential in the teaching and learning process. Storytelling skills need to be owned by elementary school teachers so that the delivery of subject can be more interesting and easy to understand. Storytelling skills can be honed with basic knowledge of the basic concepts of non-verbal communication and public speaking. The availability of the school website is a new medium for SDIT AlFirdaus Semarang in developing interesting audio-visual-based learning media, not only with one-way communication but prioritizing interactivity. The Public Speaking Training which was held at SDIT AlFirdaus Semarang was held on Monday, 5 December 2022 for two hours with 20 teachers participating. This training was not only limited to material exposure from the service team but also had direct practice of public speaking in front of the camera represented by several teachers. The benchmark for the success of the activity was carried out by completing the pre-post test where the results showed that there was an increase in knowledge of more than 70% of the training participants. This is the basis that the training activities will be easy to understand when the participants are invited to practice directly applying the theory that has been conveyed by the team of presenters of the community service activities.